Dentofacial Anomalies and Oral Hygiene Status in Mentally Challenged Children: A Survey - Rani Somani; M K Sunil; Shipra Jaidka; Jaskirat Khaira (Wolters Kluwer Medknow Publications, 2011)
Mentally compromised patients are found to be associated with various dentofacial anomalies. These patients have physical, mental, sensory, behavioral, cognitive, emotional and chronic medical conditions, which require health rare beyond considered routine. Adequate oral cleaning in them is a task because of impaired musculature. Thus, these children are prone to various oral diseases and dentofacial anomalies that require early diagnosis and treatment. This study is carried out to know the oral hygiene status and dentofacial anomalies in mentally compromised patients with an idea of helping them to have a better oral hygiene status and treat the developed dentofacial changes on time.